Regulatory barriers of circular economy adoption in construction industry: a perspective from Türkiye - Besiktepe, Deniz; Gurgun, Asli Pelin (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeEmbracing circular economy (CE) practices presents a promising pathway to promoting sustainability and improving the efficient use of limited resources and waste management in the construction industry. The purpose of this study is to explore the regulatory barriers that impede the adoption of CE practices in T & uuml;rkiye's construction industry and propose actionable strategies to overcome these challenges.Design/methodology/approachDrawing on a comprehensive literature review and a practitioner-focused survey, this study employs Importance-Adoption Quadrant Analysis (IAQA), together with descriptive and inferential statistics, to evaluate participants' perceptions regarding the significance and current implementation levels of 14 identified regulatory strategies.FindingsThe research identifies key regulatory challenges in T & uuml;rkiye, including a lack of supportive legislation, weak enforcement mechanisms and limited institutional support. Findings reveal a misalignment between the perceived importance of CE policies and their actual adoption, highlighting the need for robust financial incentives, clearly defined national targets and strategic infrastructure investments. Furthermore, statistically significant differences in perceptions of regulatory barriers across experience levels, professional backgrounds and company sectors highlight that challenges to CE adoption are highly context specific.Research limitations/implicationsThe limitations of this study stem from the selected barriers and strategies used to analyze the adoption of CE in the construction industry, as well as its focus on a single country context, T & uuml;rkiye.Originality/valueThis study advances understanding of regulatory barriers to circular economy adoption in T & uuml;rkiye's construction industry, offering new insights from a developing country context with evolving policy initiatives. By applying the Importance-Adoption Quadrant Analysis (IAQA) to regulatory strategies, the study introduces a novel methodological approach that prioritizes actionable solutions for overcoming regulatory challenges. The study contributes to theory and practice by providing a benchmark for comparative studies and delivering evidence-based recommendations for policymakers and industry practitioners to accelerate CE adoption.
Keywords: Circular economy; Construction; T & uuml; rkiye; Regulatory; Barriers; Importance-adoption quadrant analysis; BUILT ENVIRONMENT; DRIVERS; Construction & Building Technology; Science & Technology - Other Topics; Engineering